“Hostilidades da floresta”: agrodesenvolvimento e políticas agrárias no Nordeste do Pará (século XX) - SILVA, Bruno de Souza (Universidade Federal do Pará, 2025)
This thesis presents the main rural development policies that were directed towards the Amazon region from the so-called Vargas Era (1930-1945) until the end of the military government in 1985. Since these were periods of intensification in developmental policies aimed at colonization, agriculture and agroindustry through agencies such as SPVEA, BASA and SUDAM. More specifically about the experience of the population of Tomé-Açu, as it is a society that emerged from a colonization project that developed economically and politically based on black pepper agriculture, as well as constituting one of the most important institutions associations from the northeast of Pará, the Mixed Agricultural Cooperative of Tomé-Açu. Our main argument that guides this thesis is the fact that Tomé-Açu arose from policies aimed at forests, its development as well as social and economic relations had a strong influence from projects led by government agencies.